Bending analysis of functionally graded sandwich plates using HOZT including transverse displacement effects. Issue 10 (3rd October 2022) - Garg, Aman; Chalak, H. D.; Chakrabarti, Anupam
Abstract: In the present work, a novel higher-order zigzag theory is proposed for the bending analysis of sandwich functionally graded plates. Zigzag effects are incorporated with the help of a linear Heaviside step function. The present theory satisfies zero transverse shear stress conditions at the bottom and top surface of the plate along with continuity condition at interfaces for both transverse shear and transverse normal stresses. The proposed model is free from any kind of C-1 or penalty function requirements. A nine-noded isoparametric finite element having 12 degrees of freedom per node is used during analysis. Since the present theory incorporates the transverse displacement field along with continuity conditions and hence able to predict the behavior of thick sandwich plates more efficiently.